Veritable entree a l'aggregation de medecine de Bordeaux, du Sieur Rangeard docteur en medecine. - Rangeard, Jean (Chez Jean Sejourne, imprimeur & marchand libraire de l'Université, rue Saint Iames pres du marché, 1683)
A collection of statements in support of Jean Rangeard's position as physician in Bordeaux, comprising acknowledgements from the Jurat de Bordeaux of the certification of Rangeard, signed De La Cour, Jurat; support of Rangeard in Latin; evidence stating that vote of the assembly of medical practitioners held showed that the majority believed Rangeard should be recognised on the same terms as his fellow physicians.